Analysis of the integration of family farming into the national school feeding program in the north coast mesoregion of Espírito Santo - Ferreira, Matheus Pires; Santos, Lara Damasceno; Tosta, Marielce de Cassia Ribeiro (Brazilian Journal of Production Engineering, 2025)
The National School Feeding Program (PNAE) ensures healthy meals for students, contributing to academic performance through products from family farming. This project assessed the program’s effectiveness in the municipalities of Aracruz, Linhares, and São Mateus in the years 2018, 2020, and 2022. A characterization of family farmers was carried out using IBGE data; a comparative analysis of municipal bidding notices with FNDE records; an evaluation of the participation of nutritionists; and a comparison of menu macronutrients with PNAE guidelines. The results showed heterogeneity in gender, age, and race among farmers, and that 15.87% lacked access to technical information. Regarding food, there was a preference for fresh and minimally processed products, in line with PNAE guidelines and the Brazilian Dietary Guidelines. Differences were also noted between the types and prices of food reported by municipalities and the FNDE. The menus from Linhares and Aracruz did not meet the required reference levels. The average use of family farm products in schools across the three municipalities was 40.52%. The nutritionists interviewed suggested increasing the number of professionals, outsourcing labor, improving kitchen infrastructure, and acquiring new equipment.